DTPA‐extractable zinc threshold for wheat grain yield response to zinc fertilization in Mollisols. Issue 5 (17th August 2021) - Martínez Cuesta, Nicolás; Carciochi, Walter; Salvagiotti, Fernando; Sainz Rozas, Hernán; Wyngaard, Nicolás; López de Sabando, Marcelo; Barbieri, Pablo
Abstract: Determining soil Zn thresholds for wheat ( Triticum aestivum L.) is still challenging because soil Zn tests have been poorly calibrated. Therefore, this work aimed to determine, under field conditions, the diethylenetriaminepentaacetic acid (DTPA)–Zn critical threshold for wheat grain yield (GY) response to Zn fertilization in noncalcareous Mollisols. We conducted 14 Zn‐fertilization field trials in Typic Argiudolls from the Argentinean Pampas. Zinc fertilization increased GY in 6 out of 14 trials. Wheat GY response to Zn fertilization ranged from 300 to 949 kg ha –1 . Our DTPA–Zn threshold is the first one determined by field trials for wheat grown in Mollisols (1.03 mg kg −1, with a 95% confidence interval from 0.87 to 1.23 mg kg −1 ). This threshold was greater than those previously reported for other soil types. Future studies should compare different Zn‐fertilization strategies for wheat on Mollisols by combining different fertilizer rates, sources, timings, and placements. Core Ideas: Wheat grain yield response to Zn fertilization ranged from 300 to 949 kg ha −1 on Mollisols from Argentina. Diethylenetriaminepentaacetic acid–Zn adequately correlated ( r  = .77) with the wheat grain yield response to Zn fertilization. The determined DTPA–Zn critical threshold was 1.03 mg kg −1 .